Impact of Self-driving Cars for Urban Development - Aleksey Zomarev; Maria Rozhenko (Foresight and STI Governance, 2020)
The advent of self-driving vehicles is no longer just science fiction conjecture but the reality of the coming decade. Various countries have already made real progress in self-driving technologies moving beyond slogans and to meaningful action – multi-country changes in the law, for one thing. Due to the rethinking of the transport planning process and new ways to organize passengers, the urban transport system is considered a single unit, not a set of separated transport subsystems (metro, land transport, etc.). Thus far, however, there has been no extensive study of the potential urban impact of self-driving technologies upon a city and its residents.This paper presents a methodology for the urban impact assessment of self-driving transportation developed based on an appropriate analysis for the city of Moscow. To that end, the urban environment as a research subject is described as a set of environmental, transport, technological, economic, social, and regulatory blocks of indicators. We purpose to evaluate these indicators: roads congestion, need for parking spaces, changes in the employment structure, new users of automobile transport, and others.To estimate the effects on the city, we described four scenarios for the introduction of self-driving cars, differentiated by the speed of technology introduction and the development of co-using economics. To achieve maximal effect of self-driving technology, one needs to adopt a proactive transport policy, including a set of measures defined by a current survey.The survey is indispensable for future research into the impact of self-driving technology upon a city. Also, the survey has a practical sense for administrations responsibility for urban transport policy.